2015
DOI: 10.1177/0891243215599646
|View full text |Cite
|
Sign up to set email alerts
|

Forms of Femininity at the End of a Customary Marriage

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The research outlined in this article is part of a broader investigation into customary marriage and divorce in South Africa. During the larger research project (Himonga & Moore, 2015), family meetings were identified as the normative dispute resolution forum for settling marital disputes (see Button et al, 2016) but were often unable to find an agreeable resolution (Moore, 2015a). Given the fact that the larger study was focused on divorce, I was unable to say much about how family meetings assisted married spouses with a dispute.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The research outlined in this article is part of a broader investigation into customary marriage and divorce in South Africa. During the larger research project (Himonga & Moore, 2015), family meetings were identified as the normative dispute resolution forum for settling marital disputes (see Button et al, 2016) but were often unable to find an agreeable resolution (Moore, 2015a). Given the fact that the larger study was focused on divorce, I was unable to say much about how family meetings assisted married spouses with a dispute.…”
Section: Methodsmentioning
confidence: 99%
“…The participants in the study as a whole were from low socioeconomic backgrounds as defined by education and employment status. Elsewhere, I have outlined the socioeconomic status of men and women in customary marriages in South Africa (Moore, 2015a). The sample of participants was similar in this regard, and the majority of participants did not complete secondary school, were unemployed, or were involved in low-skilled, low-paid, precarious work.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations